2014
DOI: 10.4236/ajps.2014.513220
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Salicylic Acid in Tomato Leaves after Foliar Aspersions of This Compound

Abstract: Increased plant tolerance to stress may be chemically induced with applications of salicylic acid (SA). The aim of this study was to determine the change in the SA leaf concentration over time in response to the SA spraying in leaves of greenhouse grown tomato. In sprayed leaves the SA concentration showed changes over time similar to the reported responses to environmental stress. Two days after the first application, the SA foliar concentration reached the maximum of 8 µg•g −1 , equivalent to twice the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The results indicated that spraying SA or IAA at 0.25-2 mM produced significant increases in growth traits of maize plants when measured 20 DAT. The enhancing effect of SA and IAA on plant growth was reported by many investigators Guzmán-Téllez et al 2014;Khandaker et al 2018). Although, at 40 DAT, except the increment effect of 2 mM IAA on maize growth, all SA and IAA treatments did not produce any significant effect on tested growth parameters when compared with those of control.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The results indicated that spraying SA or IAA at 0.25-2 mM produced significant increases in growth traits of maize plants when measured 20 DAT. The enhancing effect of SA and IAA on plant growth was reported by many investigators Guzmán-Téllez et al 2014;Khandaker et al 2018). Although, at 40 DAT, except the increment effect of 2 mM IAA on maize growth, all SA and IAA treatments did not produce any significant effect on tested growth parameters when compared with those of control.…”
Section: Discussionmentioning
confidence: 62%
“…Although, at 40 DAT, except the increment effect of 2 mM IAA on maize growth, all SA and IAA treatments did not produce any significant effect on tested growth parameters when compared with those of control. In this concern, Guzmán-Téllez et al (2014) found some differences in the values of stem and leaves of tomato between SA treated plants (0.1 mM) and control plants at 4, 12, and 15 DAT and disappeared at the end of the assay (22 DAT). The disappearance of the enhancing effect of SA and IAA treatments in growth parameters over time may be related with the decrease in the levels of endogenous SA or IAA in treated plants by time as previously mentioned.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, for tomato, the period between application of the inducer and the effective activation of defence responses were observed within a short period, 3-7 days postinoculation [64,65]. In the same sense, Guzmán-Téllez, et al [66] reported that SA applications on tomato should be performed within a minimum interval of eight days in order to maintain SA concentration related with the increase in plant tolerance to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the SA biosynthesis is from the shikimate-phenylpropanoids pathway; SA is synthesized from phenylalanine by action of the phenylalanine ammonia lyase enzyme [8]. It has been found that the exogenous application of SA in plants induces stress tolerance, increases the biological response against salinity and extreme temperatures, modifies the concentrations of antioxidants, nutrients and chlorophyll [9] and increases the protection against pathogen attack [10]; defense is related to the attack mode and form of obtaining nutrients by the pathogen (biotrophs or necrotrophs) [11]. According to studies in Arabidopsis thaliana, defense against biotrophic pathogens usually involves dependent signaling of SA, while the induced defense against herbivorous insects and necrotrophic pathogens depend of JA [12].…”
Section: Introductionmentioning
confidence: 99%